Golden Eagle Perch-Site Use in the U.S. Southern Plains: Understanding Electrocution Risk - Dwyer, James F.; Murphy, Robert K.; Stahlecker, Dale W.; Dwyer, Angela M.; Boal, Clint W. (TTU) (Journal of Raptor Research, 2020)
© 2020 The Raptor Research Foundation, Inc. None Electrocution on overhead electric systems is a primary cause of anthropogenic mortality for Golden Eagles (Aquila chrysaetos) in North America. Distribution poles supporting energized equipment are most often involved in electrocutions, but the frequency with which Golden Eagles perch on pole supporting equipment is unknown. To resolve questions of perch frequency, and by extension, electrocution risk and mitigation prioritization, we used Google Earth to identify perch locations of GPS-transmittered preadult Golden Eagles, and specifically to identify perching on poles supporting transformers. We used transformer poles as a proxy for electrocution risk because transformers are visible in Google Earth imagery. We examined 105 randomly selected "perch events" for each of 10 Golden Eagles (n = 1050 perch events total) tracked for a mean of 16 consecutive mo after fledging. The most frequently used perch sites were cliffs (24.6%), trees (21.2%), and hills (16.6%). Across individuals, 10.8% of perches were on overhead electric systems (individual ranges = 0.0-34.3%). Seven Golden Eagles perched on a distribution pole at least once. Of these, five perched on a transformer pole at least once. Perching on transformer poles occurred more frequently than expected given the proportion of transformer poles present (Yates' χ2 = 26.5, P < 0.001). Given the frequency of perching on transformer poles revealed in this study and the frequency of electrocution on equipment poles revealed in previous studies, the data suggest that electrocution mitigation measures should be focused on equipment poles. Future research should quantify perching across a wider variety of habitats and Golden Eagle age and sex to identify whether the patterns reported here occur more broadly.